Analysis of Technical Efficiency of Public Primary Schools in Ghana: A Case Study of Ashanti Region - Aminarh, Emmanuel Sogah (2017)
A thesis presented to the Department of Economics, College of Arts and Social Sciences In partial fulfillment of the requirement for the degree of Master of Philosophy in Economics,